If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 39) = (6x + -12) Reorder the terms: (39 + 3x) = (6x + -12) Remove parenthesis around (39 + 3x) 39 + 3x = (6x + -12) Reorder the terms: 39 + 3x = (-12 + 6x) Remove parenthesis around (-12 + 6x) 39 + 3x = -12 + 6x Solving 39 + 3x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 39 + 3x + -6x = -12 + 6x + -6x Combine like terms: 3x + -6x = -3x 39 + -3x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 39 + -3x = -12 + 0 39 + -3x = -12 Add '-39' to each side of the equation. 39 + -39 + -3x = -12 + -39 Combine like terms: 39 + -39 = 0 0 + -3x = -12 + -39 -3x = -12 + -39 Combine like terms: -12 + -39 = -51 -3x = -51 Divide each side by '-3'. x = 17 Simplifying x = 17
| 2x+3y+5=0 | | (8-1)/4=2/3 | | -7x^2=21 | | 26/15=104/70-w | | 2x-12=x+12 | | 2x^2+5y^2-22=0 | | x^2-2x-2=-2x^2+9x+2 | | 6(18)-57=2(18)+15 | | 4x-2=154 | | 10-4(6)+2= | | 30x+12-10=6 | | -3(x+2)=3(x+2) | | 6-5(2-4x)=14 | | -15+10+(-6)+4= | | 8x-(x-5)+(3x+2)=x-14 | | (5x-24)=90 | | (3x-30)=90 | | 12-10= | | h=-16t^2+t | | 2x+5x-4=29 | | .04x-.05=.02x-.09 | | (8x-6)=90 | | 2x+5x=29 | | 2(x+4)=3n | | 3n-6=14+7n | | 5x+4=3x-6 | | 13=3x-1 | | 4(y-4)=1 | | -.01X^2+.04X=-98.6 | | 3x=5x+9 | | 6-3x=4x-42 | | x^3-14x^2+47x-18=0 |